2005
DOI: 10.1523/jneurosci.4097-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

L1-Mediated Branching Is Regulated by Two Ezrin-Radixin-Moesin (ERM)-Binding Sites, the RSLE Region and a Novel Juxtamembrane ERM-Binding Region

Abstract: We investigated how the neural cell adhesion molecule L1 mediates neurite outgrowth through L1-L1 homophilic interactions. Wild-type L1 and L1 with mutations in the cytoplasmic domain (CD) were introduced into L1 knock-out neurons, and transfected neurons were grown on an L1 substrate. Neurite length and branching were compared between wild-type L1 and L1CD mutations. Surprisingly, the L1CD is not required for L1-mediated neurite outgrowth but plays a critical role in neurite branching, through both the juxtam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
113
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(123 citation statements)
references
References 54 publications
10
113
0
Order By: Relevance
“…Both ankyrin-dependent and ankyrin-independent pathways are likely to operate in parallel, a conclusion supported by the incomplete rescue of neuronal growth by the AP-YF peptide after U0126 treatment ( Figure 6C). Previous work has shown that ankyrin binding to L1-CAM inhibits L1-mediated traction-force generation and neuronal growth (Gil et al, 2003;Cheng et al, 2005). The identification of the MAP kinase pathway as a regulator of L1-FIGQY phosphorylation, L1-ankyrin B interactions and L1-mediated neuronal growth reinforces the central role of ankyrin B binding in the regulated growth of neurons on L1-CAM ligands.…”
Section: Map Kinase Pathway Activity and The Regulation Of L1-cam-medsupporting
confidence: 52%
See 2 more Smart Citations
“…Both ankyrin-dependent and ankyrin-independent pathways are likely to operate in parallel, a conclusion supported by the incomplete rescue of neuronal growth by the AP-YF peptide after U0126 treatment ( Figure 6C). Previous work has shown that ankyrin binding to L1-CAM inhibits L1-mediated traction-force generation and neuronal growth (Gil et al, 2003;Cheng et al, 2005). The identification of the MAP kinase pathway as a regulator of L1-FIGQY phosphorylation, L1-ankyrin B interactions and L1-mediated neuronal growth reinforces the central role of ankyrin B binding in the regulated growth of neurons on L1-CAM ligands.…”
Section: Map Kinase Pathway Activity and The Regulation Of L1-cam-medsupporting
confidence: 52%
“…However, ankyrin binding in the growing neurite plays an inhibitory role; reagents that block L1-CAM-ankyrin interactions increase the L1-CAM-dependent growth of neurons in culture (Gil et al, 2003). Additionally, neurons expressing a truncated form of L1 that lacks the ankyrin binding site produce longer axons than neurons expressing full-length receptor, again supporting an inhibitory role for ankyrin binding in L1-mediated nerve growth (Cheng et al, 2005). Finally, the binding of ankyrin G to the L1-family member neurofascin promotes neurofascin-mediated cell adhesion .…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…α-and β-catenin in the case of N-cadherin, 10 ankyrin and ezrin in the case of IgCAMs such as L1. [11][12][13][14] These purely mechanical connections can also be accompanied by signalling events such as Rac-1 activation by N-cadherin liganding 15 and phosphorylation of the L1 intracellular tail that regulates binding to ankyrin. 11,12 When only few molecular bonds are formed, e.g.…”
mentioning
confidence: 99%
“…31 Neurite growth on L1 was estimated from references. 7,14,30 (Grey) Interaction between endogenous SynCAM1 molecules expressed on growth cones and SynCAM-Fc ligands coated on microspheres or flat glass. 16 The turnover of SynCAM homophilic interactions was estimated from SynCAM-coated Quantum dots detaching from neurons transfected with SynCAM1.…”
mentioning
confidence: 99%